Techno-Economic Analysis of On-Grid Solar Power Plants for Tulungagung Hydropower Operational Cost Savings Based on Production and Load Data (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
The increasing energy demand and environmental challenges have accelerated the global shift toward renewable energy, with Indonesia possessing a substantial solar potential of 3,294 GW. This study investigates the techno-economic feasibility of a 40.9 kWp On-Grid Solar Power Plant as a supplementary energy source to reduce operational costs at the Tulungagung Hydropower Plant. A techno-economic analysis was conducted using 2024 solar PV production data from the ShinePhone application and the Tulungagung Hydropower business daily report, complemented by simulations from the Hybrid Optimization Model for Multiple Energy Resources (HOMER) to identify optimal system configurations. The actual solar power plant generated 52,499.9 kWh/year, contributing 15.66% of the plant's operational load of 335,150.71 kWh and resulting in annual cost savings of IDR 58,523,260, based on a PLN tariff of IDR 1,114.74/kWh. In comparison, HOMER simulations projected a higher generation of 74,265 kWh/year, with a net present cost (NPC) of IDR 6,461,879,000 and a cost of energy (COE) of IDR 1,142.36. While the PLTS has proven technically and economically viable as a complementary energy source, its current capacity remains insufficient to fully meet the hydropower plant's operational load, indicating the need for further system optimization and potential integration of energy storage solutions.